Knowledge worker faire compensation: Ethical and social dilemmas! - Costa, Gonçalo Jorge Morais da (2014)
One of the key characteristics in knowledge management is the importance of human resources. Therefore, main stream literature has been discussing the concept of knowledge worker, its characteristics, and duties versus rights, and human resources policies in its dissimilar perspectives (knowledge workers retention, personal mastery, intellectual property rights, among others). Although, empirical studies seem to disregard if knowledge workers feel that are well compensated, or what dimensions entail faire compensation. Hence, this chapter aims to recognize knowledge workers feeling about faire compensation, and what elements are essential to achieve it through a conceptual framework. For that, the chapter is divided into six sections: the research questions; knowledge worker (key characteristics and responsibilities versus rights); fairness (etymology and the contribution of Rawls); linking the theoretical basis; empirical results (methodological remarks, findings and discussion); future research directions (the surrealist assumption, Dali surrealism and the metaphorical assumption).